Analisis Human Error Sebagai Upaya Pencegahan Kecelakaan Pada Bidang Maritim: Literatur Review - Diajeng Ayu Sekar Zahroh (Yayasan Daarul Huda Kruengmane, 2023)
Human error is often stated as the main factor causing an accident. For ordinary people, news about transportation accidents with human error as the cause is often interpreted as human error, system operators such as machinists, pilots, ship captains, and others. To find out the efforts to prevent ship accidents at sea due to human error. Journals/articles come from searches on the Google Scholar database, using related keywords, then journals are selected using inclusion and exclusion criteria. The year of the article in the 2020-2022 timeframe. Then the journals are analyzed one by one by looking for similarities and differences in journals and then drawing conclusions. The results of the literature review of the 5 articles obtained data regarding human error as an effort to prevent ship accidents at sea, obtaining the result that the probability of human error is high. This is due to the mistakes made by the organization as the initial defense of the defense system, not directly related to the occurrence of incidents directly but are triggers that lead to other failures leading to incidents. The SPAR-H method is a method that can be used to analyze human error and prevent ship accidents at sea. By applying this method, we can reduce the risk of ship accidents caused by human error.